Updating the “cost factor” in the William fine risk assessment method following economic power: A case study of selected production industries in Iran - Bafrin Moloudpourfard; Morteza Tahamipour Zarandi; Mostafa Pouyakian (Heliyon)
The William Fine approach is among the limited number of methods, introducing a metric referred to as the J index and discussing safety costs to evaluate control measures. Therefore, this study aimed to update the “cost factor” in the William Fine method in proportion to the economic power in selected production industries in Iran. Based on the International Standard Industrial Classification (ISIC), three selected production industries were the automotive, pharmaceutical, and food industries. The Delphi technique was used to achieve the values of safety costs in economic sectors. Due to high exchange rate fluctuations and the possibility of using the cost invoice table over time and the producer price index, the correction factor was calculated. Furthermore, the fuzzy logic method determined the cost factor of William Fine's method. The gap between the minimum and maximum costs is significantly broader in the automotive industry compared to the pharmaceutical and food industries. The cost factor correction for the automotive industry stands at 1.144, while it is 1.222 for pharmaceuticals and 1.141 for the food industry. These figures are expected to be generalized in the coming years. The present study revealed that due to the impossibility of accurate access to data related to cost performance and safety investment in industries, the Delphi method could be acceptable to achieve the range of safety costs in industries. Updating this table has enabled selected industries to achieve more accurate control costs or risk aversion estimates.